Reversal of Apixaban and Rivaroxaban Anticoagulation by Andexanet Alfa in ANNEXA-A and ANNEX-R as Assessed by Non-Tissue Factor-Initiated Thrombin Generation Independent of Tissue Factor Pathway Inhibitor. Issue 1 (11th October 2018) - Lu, Genmin; Lin, Joyce; Bronson, Michele; Crowther, Mark; Conley, Pamela B.; Curnutte, John T.
No abstract available